Multilateralism under challenge? power, international order, and structural change - Newman, Edward 1970-; Thakur, Ramesh Chandra 1948-; Tirman, John (United Nations University Press, 2006)
The principles, values and manifestations of multilateralism, including the United Nations, are under sustained scrutiny and assault. Their performance and effectiveness are questioned, as are their decision-making procedures and their representation according to 21st century standards of accountability and democracy. All this has a corrosive effect on their legitimacy. This publication explores the performance and future of multilateral approaches and institutions with reference to major global challenges such as international security, terrorism, HIV/AIDS, environmental sustainability, economic justice, human rights and humanitarian assistance.--Publisher's description.